Evaluation of a multifunctional femtosecond laser for the creation of laser in situ keratomileusis flaps. Issue 3 (March 2018) - Slade, Stephen; Ignacio, Teresa; Spector, Scott
Abstract : Purpose: : To characterize the performance of a multifunctional femtosecond laser system (Lensx) for the creation of laser in situ keratomileusis (LASIK) flaps. Setting: : Two surgical sites in the United States. Design: : Prospective case series pilot study. Methods: : Patients with myopia or hyperopia who were eligible for femtosecond laser‐initiated LASIK surgery with corrected distance visual acuities (CDVA) correctable to at least 20/25 were enrolled. Central flap thickness accuracy (desired versus achieved) and precision (flap thickness standard deviation) were measured using anterior segment optical coherence tomography. Flap dissection quality, stromal bed quality, and amount of opaque bubble layer (OBL) formation were graded during surgery, and the refractive outcomes were evaluated postoperatively at 1‐month and 3‐month follow‐ups. Results: : The study comprised 30 patients (58 eyes). At 3 months postoperatively, the flap thickness accuracy was 1.3 μm ± 2.6 (SD). A total of 78.3% of flaps were lifted with no resistance and 16.7% were lifted with minimal resistance using a blunt instrument. All (100%) stromal beds were determined to have a very smooth surface (grade 5 on a 0 to 5 scale). No OBL was observed in 73.3% of eyes; 26.7% of eyes showed an OBL occurring on less than 24% of the stromal bed surface. At 3 months postoperatively, most eyes (84.5%) had an uncorrected distance visual acuity of 20/20 and 98% had a CDVA of 20/20. The most common ocular adverse event was punctate keratitis (11.7%). Conclusion: : The multifunctional femtosecond laser system effectively created LASIK flaps that were high quality, accurate, and precise.